PELAKSANAAN STRATEGI PEMASARAN LEMBAGA PENDIDIKAN DALAM MENARIK MINAT SANTRI BARU DI PONDOK PESANTREN RAUDHATUL MUJAWWIDIN KECAMATAN RIMBO BUJANG KABUPATEN TEBO PROVINSI JAMBI - Elsa Vanny Yuli Afiatul; Armida; Ahmad Fikri (STKIP Pesisir Selatan, 2026)
This study aims to determine the implementation of educational institution marketing strategies in attracting new students at Raudhatul Mujawwidin Islamic Boarding School, Rimbo Bujang District, Tebo Regency, Jambi Province. The approach used in this research is a descriptive approach with a qualitative method. Data were collected through observation, interviews, and documentation. The data analysis techniques used in this study include data reduction, data display, and conclusion drawing (verification). The results of this study indicate that the implementation of educational institution marketing strategies in attracting new students at Raudhatul Mujawwidin Islamic Boarding School has been carried out well, as seen from the implementation process. The marketing strategies applied include mujahadah, maximizing the role of alumni, students’ parents, and community leaders as indirect promotional media, actively conducting socialization with the community, utilizing simple media, and improving service quality. Meanwhile, the inhibiting factors in attracting new students at Raudhatul Mujawwidin Islamic Boarding School consist of internal and external factors. External factors include parents’ concerns regarding issues of bullying in Islamic boarding schools. Internal factors include a lack of understanding or concern from within Raudhatul Mujawwidin itself.